A Flavonoidal-glycoside from Andrographis paniculata (Nees.) - K. Saxena, V.; Upadhyay, Shruti (Asian Journal of Chemistry, 2016)
The isolation and identification of flavonoidal glycoside from the plant Andrographis paniculata have been reported in the present paper.